Proceedings 2014 Workshop on Usable Security 2014
DOI: 10.14722/usec.2014.23006
|View full text |Cite
|
Sign up to set email alerts
|

The Privacy and Security Behaviors of Smartphone App Developers

Abstract: Abstract-Smartphone app developers have to make many privacy-related decisions about what data to collect about endusers, and how that data is used. We explore how app developers make decisions about privacy and security. Additionally, we examine whether any privacy and security behaviors are related to characteristics of the app development companies. We conduct a series of interviews with 13 app developers to obtain rich qualitative information about privacy and security decision-making. We use an online sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(157 citation statements)
references
References 6 publications
6
150
0
1
Order By: Relevance
“…The mobile application developers (''devs'') frequently responsible for making decisions about user data range from hobbyists to consultants to independent contractors to employees of multinational corporations (VisionMobile 2016). Low barriers to entry enable a vibrant but deprofessionalized development ecosystem (Cravens 2012), and surveys of application developers have revealed that many lack knowledge of current best practices for privacy and data protection (Balebako et al 2014). Devs also rely on distribution by two major international platforms: the Apple App Store and Google's Play Marketplace (VisionMobile 2016).…”
Section: Introduction: Investigating Work Dynamics That Impact Privacmentioning
confidence: 99%
“…The mobile application developers (''devs'') frequently responsible for making decisions about user data range from hobbyists to consultants to independent contractors to employees of multinational corporations (VisionMobile 2016). Low barriers to entry enable a vibrant but deprofessionalized development ecosystem (Cravens 2012), and surveys of application developers have revealed that many lack knowledge of current best practices for privacy and data protection (Balebako et al 2014). Devs also rely on distribution by two major international platforms: the Apple App Store and Google's Play Marketplace (VisionMobile 2016).…”
Section: Introduction: Investigating Work Dynamics That Impact Privacmentioning
confidence: 99%
“…Balebako et al surveyed and interviewed over 200 app developers, and concluded that most approached security issues using web search, or by consulting peers [5].…”
Section: A How Programmers Learn Securitymentioning
confidence: 99%
“…Comparing the existing work on app developers and security, section 2 identified valuable research on current practice by developers such as that by Balebako et al [5]; this work goes further by identifying approaches for better practice. Much of the remaining literature we discussed is also valuable in the context the dialectic techniques as providing solutions to the challenges identified through dialectic.…”
Section: A Relationship To Existing Workmentioning
confidence: 99%
“…Therefore, identifying the decisionmakers leads to a greater understanding of the privacy protections likely to be employed. For example, app developers without security expertise may fail to correctly implement privacy-preserving technologies (Balebako, Marsh, et al, 2014).…”
Section: Phasesmentioning
confidence: 99%